2010
DOI: 10.1111/j.1468-3156.2009.00598.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural interventions for self injurious behaviour: a review of recent evidence (1998–2008)

Abstract: Accessible summary• One in four people with a severe learning disability harm themselves.• This affects their health and quality of life.• This study looks at research on helping people who harm themselves.• More research needs to be done to find better ways of helping people who harm themselves. SummaryEstimates suggest that up to one quarter of people who have a severe learning disability engage in self injurious behaviour (SIB). SIB poses serious risks, both to the person's physical health and their quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 39 publications
(53 reference statements)
0
18
0
Order By: Relevance
“…); behavioural treatment of elopement (Lang et al . ); and behavioural treatment for self‐injurious behaviour (Prangnell ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…); behavioural treatment of elopement (Lang et al . ); and behavioural treatment for self‐injurious behaviour (Prangnell ).…”
Section: Resultsmentioning
confidence: 99%
“…) although in some cases, as noted in the latter study, evidence is limited due to a paucity of studies. The one exception was a review on behavioural interventions for self‐injurious behaviour, which found that efficacy was highly variable (Prangnell ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, there have been few studies of the long‐term efficacy of these interventions or of their effectiveness, i.e. their impact when applied in routine clinical or educational settings (Prangnell 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This study has responded to the need for more research into the effectiveness of new, non‐aversive interventions (Prangnell 2010). Staff in this study gave extremely in‐depth and well thought out responses to the questionnaire; it was clear that staff have clients’ interests at the forefront of their minds.…”
Section: Resultsmentioning
confidence: 99%